Micro-Spatial Histories of Global Labour (Springer International Publishing, 2018)
This volume suggests a new way of doing global history. Instead of offering a sweeping and generalizing overview of the past, we propose a 'micro-spatial' approach, combining micro-history with the concept of space. A focus on primary sources and awareness of the historical discontinuities and unevennesses characterizes the global history that emerges here. We use labour as our lens in this volume. The resulting micro-spatial history of labour addresses the management and recruitment of labour, its voluntary and coerced spatial mobility, its political perception and representation and the workers' own agency and social networks. The individual chapters are written by contributors whose expertise covers the late medieval Eastern Mediterranean to present-day Sierra Leone, through early modern China and Italy, eighteenth-century Cuba and the Malvinas/Falklands, the journeys of a missionary between India and Brazil and those of Christian captives across the Ottoman empire and Spain. The result is a highly readable volume that addresses key theoretical and methodological questions in historiography. Chapter 7 is open access under a CC BY 4.0 license via link.springer.com. .